THE IMPACT OF CROSS-BORDER ACQUISITIONS IN SERBIA ON PRODUCTIVITY, WAGES, AND EMPLOYMENT - Dragan, Azdejković; Dušan, Marković (Economic Annals, 2016)
Globalization created a new business environment, characterized by intensive privatization and economic liberalization. The changed business environment opened the way to increased use of crossborder acquisitions, which make the lion’s share of foreign direct investment in transition economies. The acquisitions accelerate transition, facilitating the restructuring of state-owned enterprises and making them more efficient. This paper analyses the impact of cross-border acquisitions in Serbia, an economy in transition, on employee productivity, employment, and wages in acquisition targets. Statistical analysis of a sample comprising 79 cross-border acquisitions carried out in Serbia in the period 2003-2009 shows that the change of ownership had a positive impact on employee productivity and real wages, while the number of employees in the acquired enterprises decreased.